Validation of the P-POSSUM score in predicting outcomes in emergency craniotomy: A prospective observational study - Hari Prakash Rai,; Shivam Sharma, (Asian Journal of Medical Sciences, 2024)
Background: The Portsmouth physiological and operative severity score for the enumeration of mortality and morbidity (P-POSSUM) is an established tool for predicting surgical outcomes. However, its applicability and accuracy in predicting post-operative mortality in patients undergoing emergency craniotomy require further validation. Aims and Objectives: This study aims to validate the accuracy of the P-POSSUM score in predicting post-operative mortality in patients undergoing emergency craniotomy. Materials and Methods: A prospective observational study was conducted over 2 years (June 2022–May 2024) at Maharani Laxmi Bai Medical College, Jhansi. Patients undergoing emergency craniotomy were included in the study. Data were collected on pre-operative physiological parameters and intraoperative variables to calculate the P-POSSUM score. The primary outcome was post-operative mortality within 30 days. Statistical analysis involved receiver operating characteristic curve analysis and the Hosmer-Lemeshow test to assess the predictive accuracy and calibration of the P-POSSUM score. Results: A total of 200 patients were included in the study. The mean age was 53±17 years; 113 were male and 87 were female. The P-POSSUM score demonstrated good predictive accuracy for post-operative mortality with an area under the ROC curve of 0.85 (95% CI: 0.79–0.91). Calibration analysis using the Hosmer–Lemeshow test showed good calibration (P=0.23). Observed mortality was 56 (28%) compared to an expected 61, resulting in an observed-to-expected mortality ratio of 0.92. Conclusion: The P-POSSUM score is a reliable and accurate tool for predicting post-operative mortality in patients undergoing emergency craniotomy. Its integration into clinical practice can enhance risk stratification and inform clinical decision-making. Further studies with larger cohorts and diverse populations are warranted to generalize these findings.